Kontestasi Pemikiran dalam Teologi Islam: Iman, Dosa, Perbuatan Manusia, dan Sifat Tuhan - Auria Trisi Novi Ana; Nur Zika Fauziah; Ilham Thoriq Hidayatullah (LaKaspia, 2025)
This study examines theological contestation within the tradition of Islamic kalām as an intellectual effort by Muslim scholars to articulate and systematize doctrinal teachings through rational inquiry. Central themes such as grave sin, the nature of faith, divine will, human actions, and the attributes of God represent critical points of divergence among major theological schools. Notably, the Muʿtazilite school espouses the doctrine of manzilah bayna al-manzilatayn (an intermediate status) in relation to grave sinners, while the Ashʿarites maintain that such individuals remain believers as long as they continue to affirm faith in God inwardly. Debates surrounding divine will and human agency illustrate the enduring tension between qadar (predestination) and ikhtiyār (free will) in explaining the relationship between divine sovereignty and human autonomy. Furthermore, differing interpretations of God's attributes raise complex questions about whether such attributes are independent of or identical with the divine essence. This study affirms that kalām not only functions as a guardian of theological orthodoxy but also enriches the intellectual tradition of Islam in its exploration of metaphysical and ethical dimensions.